2022
DOI: 10.1177/09564624211047679
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day readmission rates in a cohort of people living with HIV in southern Brazil, 2015 to 2017

Abstract: Background The intense use of antiretroviral therapy (ART) has reduced morbidity and mortality of HIV infection. In Brazil, the specific contribution of diseases related to HIV infection leading to hospital admission and readmission is not well known. Aims The study aimed to determine the clinico-epidemiological profile, 30-day readmission rate, and factors associated with this outcome in a cohort of adults with HIV infection in southern Brazil. Methods Unicentric retrospective cohort, with data collection thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In patients with HIV treated with ART using a controlled viral load, the immune response was related to BMI, and patients with low BMI had a lower immune response rate and longer immune function recovery time [32][33]. When CD4+ T cell count was < 200/µL, bacterial meningitis and neurosyphilis were more common, and when CD4+ T cell count was < 100/µL, common cryptococcal infection was more common-as patients with cryptococcal infection are prone to reinfection, this results in increased hospitalization [34]. Early clinical detection of individuals with lower CD4+ T cell counts, especially in patients with a baseline BMI < 18.5 kg/m 2 , and aggressive use of prophylactic therapy is essential to reduce readmission.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HIV treated with ART using a controlled viral load, the immune response was related to BMI, and patients with low BMI had a lower immune response rate and longer immune function recovery time [32][33]. When CD4+ T cell count was < 200/µL, bacterial meningitis and neurosyphilis were more common, and when CD4+ T cell count was < 100/µL, common cryptococcal infection was more common-as patients with cryptococcal infection are prone to reinfection, this results in increased hospitalization [34]. Early clinical detection of individuals with lower CD4+ T cell counts, especially in patients with a baseline BMI < 18.5 kg/m 2 , and aggressive use of prophylactic therapy is essential to reduce readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinicians could perform early pathogenetic testing, providing early intervention and comprehensive care during the first hospitalization, which helps to control infections promptly and reduce the incidence of complications. Previous studies have reported that regular follow-up after discharge, enhanced surveillance, and early outpatient intervention when problems arise can reduce the hospital readmission rate of AIDS patients [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%